2016
DOI: 10.1371/journal.pone.0162408
|View full text |Cite
|
Sign up to set email alerts
|

Segregation and Heritability of Male Sterility in Populations Derived from Progeny of Satsuma Mandarin

Abstract: Male sterility derived from Satsuma mandarin (Citrus unshiu) has been used in Japanese citrus breeding programs to obtain seedless cultivars, which is a desirable trait for consumers. Male sterility has often been evaluated by anther development or pollen fertility; however, the inheritance and heritability of male sterility derived from Satsuma is poorly understood. In this study, we investigated the mode of inheritance and broad-sense heritability of male sterility derived from Satsuma. Initially, we evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Furthermore, Satsuma is an entirely male sterile variety but Kishu and kunenbo are fertile varieties [117,133]. Goto et al recently revealed that male sterility of Satsuma is mostly caused by a decrease in pollen in the anther, and suggested the involvement of a nuclear gene to decrease pollen number [134]. The inferred parentage of Satsuma, Kishu and kunenbo with yuzu, sweet orange, sour orange, koji, tachibana and various pummelos is anticipated to enable a deep understanding of these traits of importance to the citrus industry.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Satsuma is an entirely male sterile variety but Kishu and kunenbo are fertile varieties [117,133]. Goto et al recently revealed that male sterility of Satsuma is mostly caused by a decrease in pollen in the anther, and suggested the involvement of a nuclear gene to decrease pollen number [134]. The inferred parentage of Satsuma, Kishu and kunenbo with yuzu, sweet orange, sour orange, koji, tachibana and various pummelos is anticipated to enable a deep understanding of these traits of importance to the citrus industry.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding parthenocarpic behaviour, ‘Satsuma’ is known as a natural obligatory parthenocarpic mandarin, and can set fruit without any external stimulus, whereas ‘Clementine’ is a facultative parthenocarpic mandarin that requires pollen stimulation in order to set fruit . In addition to parthenocarpy, other genetically inherent traits which allow production of seedless fruit or influence seed number are male/female sterility and self‐incompatibility . For example, some ‘Satsuma’ varieties possess cytoplasmic male sterility (CMS) that results in abortion of anthers during initial stages of development before pollen production .…”
Section: Fruit Quality Traitsmentioning
confidence: 99%
“…Their seedlings were grafted onto trifoliate orange rootstock as a single replicate in April 2012. The details about grafting and cultivation were described in our previous report [ 14 ]. The NPG and APF of individual seedlings in the O46-O56 and the O46-K populations in 2014 and 2015 were evaluated previously [ 14 , 20 ] and those in the O46-O56 in 2016 were newly evaluated in this study ( S1 Table ).…”
Section: Methodsmentioning
confidence: 99%
“…1 (G1), was regenerated [ 8 ] and confirmed to be male-sterile and seedless with a severe degeneration of stamen and petals [ 11 , 12 ] and aborted pollen grains in anthers [ 13 ]. In contrast, our recent study indicated that both the number of pollen grains per anther (NPG) and the apparent pollen fertility (APF) of male-sterile varieties, which are used to compute the index of male sterility, are inherited by their progeny and suggested the involvement of a nuclear factor [ 14 ]. This study also suggested that the cooperative action of the cytoplasm derived from Satsuma and the nuclear gene(s) is a prerequisite for the expression of NPG [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation